Effect of cardiac resynchronization therapy with implantable cardioverter defibrillator versus cardiac resynchronization therapy with pacemaker on mortality in heart failure patients: results of a high‐volume, single‐centre experience. (7th November 2014) - Kutyifa, Valentina; Geller, Laszlo; Bogyi, Peter; Zima, Endre; Aktas, Mehmet K.; Ozcan, Emin Evren; Becker, David; Nagy, Vivien Klaudia; Kosztin, Annamaria; Szilagyi, Szabolcs; Merkely, Bela
<x xml:space="preserve">Abstract</x> Aims There are limited and contradictory data on the effects of CRT with implantable cardioverter defibrillator (CRT‐D) on mortality as compared with CRT with pacemaker (CRT‐P). Methods and results We evaluated the long‐term outcome of patients implanted with a CRT‐D or CRT‐P device in our high‐volume single‐centre experience. Data on all‐cause mortality were derived from clinic visits and the Hungarian National Healthcare Fund Death Registry. Kaplan–Meier survival analyses and multivariate Cox regression models were used to evaluate all‐cause mortality in patients with CRT‐D vs. CRT‐P, stratified by the aetiology of cardiomyopathy. From 2000 to 2011, 1122 CRT devices, 693 CRT‐P (LVEF 28.2 ± 7.4%) and 429 CRT‐D (LVEF 27.6 ± 6.4%), were implanted at our centre. During the median follow‐up of 28 months, 379 patients died from any cause, 250 patients (36%) with an implanted CRT‐P and 129 patients (30%) with an implanted CRT‐D. There was no evidence of mortality benefit in patients implanted with a CRT‐D compared with a CRT‐P in the total cohort [hazard ratio (HR) 0.98, 95% confidence interval (CI) 0.73–1.32, P = 0.884]. In patients with ischaemic cardiomyopathy, CRT‐D treatment was associated with a significant 30% risk reduction in all‐cause mortality compared with an implanted CRT‐P (HR 0.70, 95% CI 0.51–0.97, P = 0.03). In non‐ischaemic patients, there was no mortality benefit of CRT‐D over CRT‐P (HR 0.98, 95% CI 0.73–1.32, P = 0.894, interaction P‐value = 0.15). Conclusions In heart failure patients with ischaemic cardiomyopathy, CRT‐D was associated with a mortality benefit compared with CRT‐P, but no benefit of CRT‐D over CRT‐P in mortality was observed in non‐ischaemic cardiomyopathy.